BEGENDANG BESERUNAI: INTEGRATION OF TRADITIONAL VALUES IN THE CREATION OF BENGKULU KARAWITAN MUSIC COMPOSITION - Arnailis Arnailis; Yunaidi Yunaidi; Firman Firman; Muhammad Zulfahmi (LPPM Institut Seni Indonesia Padangpanjang, 2025)
The work “Begendang Beserunai” is a contemporary karawitan music composition inspired by the musical phenomenon of the gendang serunai, one of Bengkulu’s traditional arts that plays an important role in ceremonial processions and community entertainment. The gendang serunai, consisting of two long drums (melalu and ningkah) and a serunai as the melody carrier, is distinctive for its interlocking rhythmic patterns and melodic motifs in a scale close to a-b-c-d-e-f#-g-a’. This creation aims to preserve the essence of tradition while introducing innovation through techniques such as unison, canon, polyrhythmic, responsorial, polymetric, and accentuation, supported by additional instruments such as dol, kompang, kolintang, accordion, bass guitar, and cymbals. The method used is a mixed methods approach combining qualitative methods—through participatory observation, in-depth interviews, and recording analysis—and quantitative methods—through measuring tempo, dynamics, rhythmic pattern duration, and audience questionnaires. The results show that this work successfully integrates traditional musical idioms into a modern composition format while maintaining its identity. Questionnaire analysis (n = 50) shows that 84% of respondents perceived the traditional nuance as strong, while 78% rated the aesthetic appeal as high. This work contributes to cultural preservation through documentation, education, and artistic innovation relevant to the contemporary context. “Begendang Beserunai” serves as a model for developing tradition-based works applicable to other regional music forms, as well as an academic and artistic reference for artists, researchers, and art education institutions.